Defect-dependent stability of highly propylene-selective zeolitic-imidazolate framework ZIF-8 membranes - Lee, Moon Joo; Kwon, Hyuk Taek; Jeong, Hae-Kwon (Journal of membrane science, 2017)
Membranes of ZIF-8, a prototypical zeolitic-imidazolate framework (ZIF) with a sodalite topology, have shown excellent propylene/propane separation performances based on molecular sieving mechanism. Although the long-term stability of ZIF-8 membranes is of critical importance for their practical applications, there are only a few studies reported on the subject. Here, we report the long-term binary propylene/propane performances of ZIF-8 membranes prepared by two distinctive synthesis methods. A series of characterizations was employed to explain how different synthetic protocols led to the formation of ZIF-8 membranes with different bulk defect densities and surface defects, thereby affecting the long-term membrane stability. Finally, a post-synthetic ligand treatment is proposed as an effective means to mitigate the defects of ZIF-8 membranes, resulting in improved long-term separation performances.